2016
DOI: 10.1055/s-0036-1583270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical and Intravenously Applied Tranexamic Acid Compared to Control Group on Bleeding in Primary Unilateral Total Knee Arthroplasty

Abstract: We aimed to answer the following three questions in this study: (1) Does tranexamic acid (TA) reduce the amount of bleeding in total knee arthroplasty (TKA)? (2) Does TA reduce requirement for blood transfusion? (3) Is there any difference on reliability and efficacy between topical and intravenous (IV) applications of TA? Patients were allocated into three groups randomly by a software program as topical, IV, and control group. TA was applied as 20 mg/kg to the IV group and as 3 g/100 mL saline to the topical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Four trials 16,32,35,39 were found to have a low risk of bias and 11 trials 17,31,33,34,[36][37][38][40][41][42][43] were found to have a high risk of bias (►Fig. 2).…”
Section: Risk Of Biasmentioning
confidence: 99%
See 3 more Smart Citations
“…Four trials 16,32,35,39 were found to have a low risk of bias and 11 trials 17,31,33,34,[36][37][38][40][41][42][43] were found to have a high risk of bias (►Fig. 2).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Adequate randomized sequence was generated in 14 trials, 16,17,[31][32][33][34][35][36][37][38][39][41][42][43] and appropriate allocation concealment was reported in 12 trials. 16,17,31,32,34,35,[37][38][39][41][42][43] Blinding of participants and outcome assessors was clear only in four trials. 16,32,35,39…”
Section: Risk Of Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…17 There are evidences for use of intravenous or topical tranexamic acid to reduce perioperative blood loss and transfusion in major orthopedic surgery. 26,27 Tranexamic acid also attenuated fibrinolysis aggravated by colloid. 28 Fourth, FIB-TEM values are higher in patients with a lower (<36%) hematocrit than in patients with higher hematocrit values.…”
Section: Discussionmentioning
confidence: 87%